Prevalence and Risk Factors Associated with Anaemia Amongst Adolescent Girls Attending in Pediatrics OPD of Nepalgunj Medical College - Ahmad, Shakil (Journal of Nepalgunj Medical College, 2017)
Background: The habits that children inculcate during adolescence remains with them throughout the life. Anaemia is one of the most prevalent health conditions amongst the Girls residing in developing countries. The present study was conducted with the aim to determine the prevalence and risk factors associated with anaemia amongst adolescent girls attending in paediatrics OPD of Nepalgunj Medical College. Materials and methods: The present cross sectional study was performed for a period of one year (February 2016 - March 2017). This study was conducted amongst the girls attending to the Paediatrics department of Nepalgunj Medical College and Teaching Hospital, Nepalgunj. The study included all the girls aged between 10-19 years. Each Girls underwent physical examination under trained supervision to record sign of anaemia like pallor. Body mass index of all the subjects was also calculated. The data obtained was arranged in a tabulated form and analysed using SPSS software. Results: A total of 200 girls were enrolled in this study. The mean age of the study sample was 21.10+/-10.67 years. Majority of the early adolescents (68.5%) had anaemia. Least number (36%) of anaemic patients was seen in mid adolescence. There were 47.5% girls in late adolescence that showed signs of anaemia. There were 47.9% Girls who had passage of worms and 50.1% had no worm infestations. Majority (63.5%) of non anaemic Girls were in their post menarche stage. Conclusion: There were 52% of the girls who were anaemic in our study. The proportion of undernourished girls were significantly higher, therefore body mass index significantly affects anaemia.